2020
DOI: 10.1002/acp.3767
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic review of the timing for disclosing evidence when interviewing suspects

Abstract: This meta‐analytic review examines the most fundamental question for disclosing evidence during suspect interviews: What are the effective options for when to disclose the available evidence? We provide an update to Hartwig and colleagues (2014) meta‐analysis of the efficacy of the late and early disclosure methods on eliciting statement‐evidence inconsistencies from guilty and innocent suspects. We also extend these analyses to include studies comparing gradual disclosure to early and late disclosure when int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 51 publications
(169 reference statements)
2
33
0
Order By: Relevance
“…Several suspect interviewing techniques that can facilitate credibility assessments are then evaluated, including the timing of evidence disclosure (Oleszkiewicz & Watson, 2021) and the Scharff interrogation technique (Luke, 2021). Recent research has examined both strategic and tactical approaches to the disclosure of evidence – tactics that are believed to facilitate statement‐evidence inconsistencies from guilty versus innocent suspects and to potentially facilitate the disclosure of novel information.…”
Section: Synthesizing the Investigative Interview Research Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Several suspect interviewing techniques that can facilitate credibility assessments are then evaluated, including the timing of evidence disclosure (Oleszkiewicz & Watson, 2021) and the Scharff interrogation technique (Luke, 2021). Recent research has examined both strategic and tactical approaches to the disclosure of evidence – tactics that are believed to facilitate statement‐evidence inconsistencies from guilty versus innocent suspects and to potentially facilitate the disclosure of novel information.…”
Section: Synthesizing the Investigative Interview Research Literaturementioning
confidence: 99%
“…First, authors of these reviews resoundingly called for important considerations for future research and data collection practices. For example, many of the reviews focused on relatively small literatures that could benefit from more experimental research and improved power in research designs (with cells sizes often too small to detect appropriate effect sizes; (Gabbert et al, 2021;Horry et al, 2021;Luke, 2021;Oleszkiewicz & Watson, 2021;Otgaar et al, 2021;Verschuere et al, 2021). In some instances, replication of findings was encouraged to extend beyond well-defined research groups (Luke, 2021;Verschuere et al, 2021).…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking forward, the future of the practice of investigative interviewing centers around the reliability of both the underlying research and how that research is translated into strategies and tactics. Toward that end, even well-established, evidence-based stratagems require continued study and occasional review to build confidence in their utility (see Horry et al, 2021;Mac Giolla & Luke, 2021;Oleszkiewicz & Watson, 2021). I would like to end with a reminder that investigative interviewing must be viewed not just as a system with interacting agents and emergent properties, but as a system of systems.…”
Section: Science As a Lens To The Past And To The Futurementioning
confidence: 99%
“…In most real-life situations criminal investigators already have collected information that implicates the suspect to some extent before they start interviewing him/her (Hartwig et al 2006;Hoekendijk and van Beek 2015). Disclosure strategies (Bull 2014;Oleszkiewicz and Watson 2020) address the questions of when and how interviewers should present the suspect with this already collected information. A growing body of research has found that a strategy of late or gradual disclosure of aspects of the evidence/information seems to outperform early or no disclosure in terms of being able to collect further relevant information from suspects (Walsh and Bull 2015), to corroborate on existing information (Tekin et al 2016), to evaluate the veracity of statements made by the suspect (Sandham et al 2020;Dando et al 2015;Dando and Bull 2011), to assess verbal cues to deceit (Hartwig et al 2005), to obtain and assess statementevidence inconsistencies (Clemens et al 2011;Oleszkiewicz and Watson 2020), and to obtain admissions (Tekin et al 2015) or confessions (Bull and Soukara 2010).…”
Section: Introductionmentioning
confidence: 99%